Új állattenyésztési ágazat Magyarországon : a tejhasznú bivaly - Bodnár, Károly; Makra, László; Bodnárné Skobrák, Erika (Közép-Európai Közlemények, 2017)
A new animal production sector appeared in the Hungarian agriculture this year: the dairy buffaloes. The species (Bos bubalus domesticus) is not new in Eastern Europe, but the Carpathian type buffalo and those from the Balkan countries have three main purposes: use in yoke, meat production, and some milk production. But the animals have more muscle (strength) than beef or milk. In Italy a dairy type Mediterranean buffalo breed was selected with larger body capacity and a significantly higher milk production. The milk which is produced by this animals is the basis of the famous Italian buffalo mozzarella (la mozzarella di bufala). A Hungarian-Italian joint venture (Italiagro Kft.) imported Italian 60 pregnant dairy buffaloes and bull to Hungary and begin to produce milk and cheese in the town of Mezőtúr. Recent study is about construction, the start of the buffalo farm and the supply chain which was built up.